Why did the Canada goose cross the sea? Accounting for the behaviour of wildlife in the documentary series Life. (15th January 2013) - Sealey, Alison; Oakley, Lee
<x xml:space="preserve">Abstract</x> The language investigated here comprises commentaries to a television documentary series about wildlife. We explore debates about the implications of evolutionary theory for accounts of animals' behaviour, and the challenge facing broadcasters seeking to explain this to a general audience. Our analysis, which was supported by concordancing software, focuses specifically on deontic and dynamic modal constructions. We identify four kinds of 'obligation' to which the non‐human creatures featured in these texts are represented as being subject. We suggest that the modal system of English is implicated in the inevitable tendency in these broadcasts towards both anthropomorphic and teleological explanations of animals' behaviour. We conclude that applied linguists have a contribution to offer as broadcasters make decisions about such linguistic choices.